(untitled) (International Seven Journal of Health Research, 2024)
Introduction: Adolescence is a phase of life full of emotional, cognitive, social and hormonal transformations, as well as changes in affective relationships between young people and their experience of sexuality. In view of this, connecting education and health is essential for sharing information, identifying users’ health needs and fostering individuals’ autonomy, so that their choices can be more appropriate, as well as reducing the distance between health professionals and the population. Methodology: This is a descriptive experience report from an extension group, whose main audience was students at a full-time secondary school in the municipality of Quixadá, Ceará. The interventions took place from August 2023 to October 2023. The actions involved an educational blitz, lectures and active methodologies on various topics. In addition, an Instagram social network profile was created to publicize the project’s actions and educational-formative content, which enabled a greater reach. The actions were divided into five themes: Educational blitz on the culture of peace; Bullying and Fake news; Negative impacts of alcohol and drug use in adolescence; Mental health; STIs in adolescence. Result: The actions on bullying and the Yellow September action began with a brief explanation of the subject, which helped the students to learn about the topic and those who already knew about it to reaffirm the concept. Later, at the end of the explanation, the students were able to ask questions and share experiences, which made the action more interactive, enriched the debate and enabled a mutual exchange of knowledge. On the other hand, the educational blitz on the culture of peace in schools took a different approach, using pamphlets with the numbers of violence among the public and its impact on the future, so that the young people approached were impacted and recognized the importance of implementing a culture of peace in schools. Finally, the project helped to strengthen the school-university relationship by improving the quality of life of young people, breaking down barriers in the classroom, especially when it came to mental health.